2023
DOI: 10.3389/fnbeh.2022.1006065
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating depression- and anxiety-like behaviors in non-human primates

Abstract: Depression and anxiety are some of the most prevalent and debilitating mental health conditions in humans. They can present on their own or as co-morbidities with other disorders. Like humans, non-human primates (NHPs) can develop depression- and anxiety-like signs. Here, we first define human depression and anxiety, examine equivalent species-specific behaviors in NHPs, and consider models and current methods to identify and evaluate these behaviors. We also discuss knowledge gaps, as well as the importance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 147 publications
0
3
0
Order By: Relevance
“…Humans are most closely evolutionarily related to other simian species, including Old World Monkeys and New World Monkeys, which diverged ~30 and ~50 million years ago, respectively (Stevens et al, 2013 ; Yang et al, 2021a ). Macaques (Old World) and marmosets (New World) are the two most commonly used NHP species in anxiety research (Ausderau et al, 2023 ); each have a distinct utility for studying aspects of anxiety and fear based on their ethology and ecological niche (Capitanio, 2017 ; Capitanio & Emborg, 2008 ; Gunnar et al, 2015 ; Kalin & Shelton, 2003 ; Machado & Bachevalier, 2003 ; Miller et al, 2016 ; Mitchell & Leopold, 2015 ; Okano, 2021 ; Saito, 2015 ). NHPs have been leveraged to confirm the evolutionary conservation of brain-behavior relationships for many threat-relevant regions (Agustín-Pavón et al, 2012 ; Fox, Oler, Shackman et al, 2015a ; Izquierdo et al, 2005 ; Kalin et al, 2004 , 2007 ; Kenwood & Kalin, 2021 ; Machado & Bachevalier, 2008 ; Prather et al, 2001 ; Shiba et al, 2015 ).…”
Section: Capturing Fear and Anxiety Across Species: The Value Of Nont...mentioning
confidence: 99%
“…Humans are most closely evolutionarily related to other simian species, including Old World Monkeys and New World Monkeys, which diverged ~30 and ~50 million years ago, respectively (Stevens et al, 2013 ; Yang et al, 2021a ). Macaques (Old World) and marmosets (New World) are the two most commonly used NHP species in anxiety research (Ausderau et al, 2023 ); each have a distinct utility for studying aspects of anxiety and fear based on their ethology and ecological niche (Capitanio, 2017 ; Capitanio & Emborg, 2008 ; Gunnar et al, 2015 ; Kalin & Shelton, 2003 ; Machado & Bachevalier, 2003 ; Miller et al, 2016 ; Mitchell & Leopold, 2015 ; Okano, 2021 ; Saito, 2015 ). NHPs have been leveraged to confirm the evolutionary conservation of brain-behavior relationships for many threat-relevant regions (Agustín-Pavón et al, 2012 ; Fox, Oler, Shackman et al, 2015a ; Izquierdo et al, 2005 ; Kalin et al, 2004 , 2007 ; Kenwood & Kalin, 2021 ; Machado & Bachevalier, 2008 ; Prather et al, 2001 ; Shiba et al, 2015 ).…”
Section: Capturing Fear and Anxiety Across Species: The Value Of Nont...mentioning
confidence: 99%
“…1,2,37,38 In this vein, McLaughlin and colleagues (2019) 39 have explored the neurodevelopmental mechanisms that underlie the boundary between adverse childhood experiences (ACE) in children and psychopathological outcomes in adulthood, including PTSD, major depressive episodes, anxiety, and cognitive impairment. Likewise, Ausderau and colleagues (2023) 40 compared the symptoms of depression and anxiety between humans, marmosets, Rhesus and long-tailed macaques. The vast majority of cited papers on this research focused on severe life experiences and their role in the development of aforementioned disorders, such as maternal separation, [41][42][43][44][45] early social withdrawal, 46,47 and early adverse rearing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Anxiety-like behavior is an evolutionarily conserved behavior observed in different species, including mammals and fish (Ausderau et al 2023 ; Lang et al 2000 ; Kysil et al 2017 ). Several studies have demonstrated that Danio rerio (zebrafish) represents a powerful model to evaluate mechanisms controlling altered behavior such as anxiety (Assad et al 2020 ; Kalueff et al 2014 ; Maximino et al 2011 ).…”
Section: Introductionmentioning
confidence: 99%